Exploring the adaptive role of core social motives in perceived societal threats - Kashima, E.S.; Ochoa, D.P; Nicolas, G.; Getrude C. Ah Gang @Grace; Du, H.; Klackl, J.; Plusnin, N.; Miriyagalla, U.P.; Kashima, Y.; Fiske, S.T. (Blackwell Publishing Ltd, 2021)
Societal threats that face the world today seem overpowering, especially for young generations who will need to develop creative solutions. The present study examined the relationships between societal threats and social motives. Social motives function to orient individuals toward the social world and prepare them to engage socially. This adaptive function of social motives may be particularly useful when threats are looming in the environment. We thus expected that perceived societal threats would correlate positively with activation of social motives, especially among individuals with lower self-esteem, who tend to show higher interdependency when threatened. Our cross-cultural samples from Australia, the United States, New Zealand, the Philippines, China (Macao), Malaysia (Sabah), and Austria (N = 1,269) showed evidence to support these expectations. Perceived societal threats correlated positively with all social motives (Belong, Understand, Control, Esteem, and Trust); however, the link was most vital for the Control motive, and especially in the United States and China. In line with our expectations, higher perceived societal threats were associated with more robust social motives, especially among those with low self-esteem. Potential mechanisms through which social motives assist adaptation to societal threats and country-specific contents of threats are discussed.